Strategic Orientations, Knowledge Acquisition, and Firm Performance: The Perspective of the Vendor in Cross‐Border Outsourcing - Li, Yuan; Wei, Zelong; Liu, Yi (Journal of Management Studies, 2010)
abstractFrom the perspective of the vendors in emerging countries (VECs), this article investigates how the vendor firms in China respond to cross‐border outsourcing trends differently by examining the different effects of entrepreneurial orientation (EO) and market orientation (MO), as well as their interaction, on local vendors' acquisition of knowledge from foreign outsourcers in cross‐border outsourcing. We find that the knowledge acquisition of the vendors positively affects firm performance. Thus, the vendors need to correctly choose their strategic orientation to improve the knowledge acquisitions. Our results show the EO of the vendors has a positive effect on the knowledge acquisition, but the relationship between MO and the knowledge acquisition is an inverted U‐shape. Further, the interactive effect between EO and MO on the knowledge acquisition is positive. All these findings extend the literature in organizational learning and cross‐border outsourcing, and suggest that VECs should not only correctly choose their strategic orientation, but also pay more attention to the orientation interaction in acquiring knowledge from their partners through cross‐border outsourcing so that they can more efficiently improve their performance.